A autoafirmação de um Bispo: Gregório de Nissa e sua visão condenatória aos Eunomianos (360-394 d.C.) - Papa, Helena Amália [UNESP] (2014)
Considering the plurality of politico-theological discussions that occurred in the 4th century AD, this research focuses on one that was intended to give consistency and meaning to the doctrine of the Trinity. Two Christian groups, each of which had different views on this issue, practiced discussions about the divinity of the second person of the Trinity, Jesus Christ. It was a dispute between Arian Christians and Nicene Christians, personified in this investigation by the Bishops, Gregory of Nyssa (335/340-394 AD) and the Arian, Eunomius of Cyzicus (335-394 AD). Our broader intention was to analyze the intricacies of the production and circulation of the discourse Adversus Eunomium (Book 1), by Gregory of Nyssa, in order to comprehend the relation of power that complemented and contrasted with the goal of being accepted as correct (orthodox) by their peers and by the Emperor, at a time that Christianity itself and, consequently their hierarchical organization were strengthening themselves. The conflict is presented as an appendix to the historiography of another quarrel which ensued around two decades before: between the same Arian Eunomius of Cyzicus and Bishop Basil of Caesarea (AD 329/331-378), brother of the aforementioned Bishop Gregory of Nyssa. Thus, the hypothesis of this thesis is that Gregory of Nyssa wrote his speech Against Eunomius as a form of self-promotion and self-assertion in order to re-establish his image among the Nycians, after Gregory faced a period of exile, imprisonment and a consequent physical distance from the politico-religious game that occurred in that context. In addition, about three years after his exile, Gregory of Nazianzus gained acceptance into the Imperial Court of Theodosius I, who selected him for a position that dealt with political and religious matters. In order to understand Gregory of Nazianzus's self-assertion with regards to this context, and...